The gcm-motif: A novel DNA-binding motif conserved in Drosophila and mammals - Akiyama, Yasuko (The National Academy of Sciences of the USA, 1996)
In the Drosophila nervous system, the glial cells missing gene (gcm) is transiently expressed in glial precursors to switch their fate from the neuronal default to glia. It encodes a novel 504-amino acid protein with a nuclear localization signal. We report here that the GCM protein is a novel DNA-binding protein and that its DNA-binding activity is localized in the N-terminal 181 amino acids. It binds with high specificity to the nucleotide sequence, (A/G)CCCGCAT, which is a novel sequence among known targets of DNA-binding proteins. Eleven such GCM-binding sequences are found in the 5′ upstream region of the repo gene, whose expression in early glial cells is dependent on gcm. This suggests that the GCM protein is a transcriptional regulator directly controlling repo. We have also identified homologous genes from human and mouse whose products share a highly conserved N-terminal region with Drosophila GCM. At least one of these was shown to have DNA-binding activity similar to that of GCM. By comparing the deduced amino acid sequences of these gene products, we were able to define the “gcm motif,” an evolutionarily conserved motif with DNA-binding activity. By PCR amplification, we obtained evidence for the existence of additional gcm-motif genes in mouse as well as in Drosophila. The gcm-motif, therefore, forms a family of novel DNA-binding proteins, and may function in various aspects of cell fate determination.